Prediction of soil shear strength in agricultural and natural environments of the Brazilian Cerrado - Silva, Reginaldo Barboza da; Dias Junior, Moacir de Souza; Iori, Piero; Silva, Francisca Alcivânia de Melo; Folle, Sergio Mauro; Franz, Claudio Alberto Bento; Souza, Zigomar Menezes de (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to develop uni‑ and multivariate models to predict maximum soil shear strength (tmax) under different normal stresses (σn), water contents (U), and soil managements. The study was carried out in a Rhodic Haplustox under Cerrado (control area) and under no‑tillage and conventional tillage systems. Undisturbed soil samples were taken in the 0.00–0.05 m layer and subjected to increasing U and σn, in shear strength tests. The uni‑ and multivariate models – respectively tmax=10(a+bU) and tmax=10(a+bU+csn) – were significant in all three soil management systems evaluated and they satisfactorily explain the relationship between U, σn, and tmax. The soil under Cerrado has the highest shear strength (t) estimated with the univariate model, regardless of the soil water content, whereas the soil under conventional tillage shows the highest values with the multivariate model, which were associated to the lowest water contents at the soil consistency limits in this management system.